The aquatic Heteroptera (Insecta: Hemiptera) of the "Foreste Casentinesi, Monte Falterona e Campigna" National Park (Central Italy) - Cianferoni, Fabio; Mazza, Giuseppe (Zootaxa, 2012)
We provide the first checklist of the aquatic Heteroptera of the “Foreste Casentinesi, M. Falterona e Campigna” National Park, located on the Apennines between Tuscany and Emilia-Romagna. We list 31 species, representing the 28% of the aquatic Hemiptera present in Italy. We summarize data on Gerromorpha (14 spp.), Nepomorpha (13 spp.) and water-dependent Leptopodomorpha (4 spp.) of this protected area, reporting for each species all sampling data.